Spectrophotometric Determination of Oxidative Coupling Reactions of Nebivolol and Trandolapril - SUBBAYAMMA, A.V.; RAMBABU, C. (Asian Journal of Chemistry, 2010)
Simple and sensitive spectrophotometric methods (M1-M3) by the application of oxidative coupling reactions for the assay of nebivolol and trandolapril have been described. Methods M1, M2 and M3 involve the oxidative coupling reactions of nebivolol with (2,3- dimethoxystricychridin- 10-one) (Brucine) (Bru) (Method M1, λmax 520 nm) or 3-methyl- 2-benzothiozolinone hydrazone (MBTH) (Method M2, λmax 620 nm) in the presence of periodate. Method M3 is based on the oxidative coupling of trandolapril with Brucine (Method M3, λmax 520 nm) in the presence of periodate. Regression analysis of Beer's law plot showed good correlation in the concentration range of 6-36, 2-12, 6-36 μg/mL for methods M1, M2 and M3, respectively. The molar absorptivities lie within the range of 0.0728 × 105–0.2118 × 105 1 mol-1 cm-1 and reproducible with an accuracy of ± 1 %.